RENDAHNYA PERAN SISTEM KADERISASI POLITIK DI DPD PSI KOTA SEMARANG: STUDI PADA CALON ANGGOTA LEGISLATIF PEREMPUAN - Pungky Kumala Sari; Kushandajani Kushandajani (Journal of Politic and Government Studies, 2026)
Women's representation politics has a foundation of affirmative action policies that require 30% representation in legislative nominations. The Indonesian Solidarity Party (PSI) showed encouraging results in the 2024 Election by passing three female legislative candidates to the Semarang City Council. This study aims to analyze the role of the regeneration system implemented by the Semarang City PSI Regional Representative Council in preparing female cadres and examine the implications of the dynamics of the regeneration system on women's political participation, access, and capacity. The research method uses a descriptive qualitative approach with data collection through in-depth interviews with PSI administrators, cadres, and legislative members. Data were analyzed using gender politics theory and cadre theory. The results show that the PSI recruitment system is open and inclusive, providing broad access for anyone who wants to join. However, the formal recruitment mechanism and cadre system have not sufficiently helped members gain adequate organizational access and capacity. There is no strict, standardized curriculum, and training frequency is incidental, following political momentum. The success of three female PSI candidates in Semarang City was more influenced by individual capacity than by intervention from the cadre system. PSI has succeeded in fulfilling the administrative quota for women's representation, but strengthening organizational structures and formalizing cadre development needs to be improved to ensure sustainable women's political participation.